PENERAPAN METODE TILAWATI DALAM PEMBELAJARAN MEMBACA ALQUR’AN PADA ANAK USIA DINI DI KB TAAM ADINDA MENGANTI GRESIK - Syaikhon, Muhammad (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2017)
Based on the focus of the problem above, the purposes of this study are: (1) To know the approach applied in learning of reading Al-Qur'an using tilawati method at students of KB Taam Adinda Menganti Gresik. (2) To know the evaluation in learning to read Al-Qur'an using tilawati method at the students of KB TAAM Adinda Menganti Gresik.This research is a kind of field research with qualitative descriptive approach. The findings of this study can be concluded that: The approach in learning the Qur'an using tilawati method is done by using two techniques, namely classical and individual techniques. The approach in the Qur'an learning using tilawati method is done through 4 techniques, namely classical technique 1 (teacher reads and students listen), classical technique 2 (teacher reads and students follow), classical technique 3 (teacher and student read together) And reading and listening techniques (one reads and the others listen). From the four techniques above, KB TAAM Adinda Menganti Gresik only uses the third technique, for classical using the visuals and reading one page at each meeting. While individual approache using private or sorogan techniques when reading volumes only. While Evaluation in learning of Al-Qur'an using tilawati method in KB TAAM Adinda Menganti Gresik there are 3 (three) types, namely Pre test, daily, and volume binding.